Base Catalytic Approach: A Promising Technique for the Activation of Biochar for Equilibrium Sorption Studies of Copper, Cu(II) Ions in Single Solute System - Hamid, Sharifah Bee Abdul (Materials (Basel), 2014)
This study examines the feasibility of catalytically pretreated biochar derived from the dried exocarp or fruit peel of mangostene with Group I alkali metal hydroxide (KOH). The pretreated char was activated in the presence of carbon dioxide gas flow at high temperature to upgrade its physiochemical properties for the removal of copper, Cu(II) cations in single solute system. The effect of three independent variables, including temperature, agitation time and concentration, on sorption performance were carried out. Reaction kinetics parameters were determined by using linear regression analysis of the pseudo first, pseudo second, Elovich and intra-particle diffusion models. The regression co-efficient, R(2) values were best for the pseudo second order kinetic model for all the concentration ranges under investigation. This implied that Cu(II) cations were adsorbed mainly by chemical interactions with the surface active sites of the activated biochar. Langmuir, Freundlich and Temkin isotherm models were used to interpret the equilibrium data at different temperature. Thermodynamic studies revealed that the sorption process was spontaneous and endothermic. The surface area of the activated sample was 367.10 m(2)/g, whereas before base activation, it was only 1.22 m(2)/g. The results elucidated that the base pretreatment was efficient enough to yield porous carbon with an enlarged surface area, which can successfully eliminate Cu(II) cations from waste water.